Analysis of Leadership Development on Employee Performance through Job Commitment as a Mediating Variable - Nurhalimah, Sifa; Ramdan, Asep Muhamad; Mulia Z, Faizal (Dinasti Publisher, 2024)
Human resources are considered an important asset, therefore, companies must ensure the quality of sustainable work life and employee development so that they can contribute optimally in achieving company goals. This study aims to determine the effect of Leadership Development, and Work Commitment on employee performance and the effect of Work Commitment in mediating the relationship between Leadership Development and Employee Performance. The research method carried out is a quantitative research method with a causal descriptive approach. The object of this research is Leadership Development, Employee Performance and Work Commitment. The population in this study were employees of PT Pawnshop Sukabumi Branch. The sampling technique used was probability sampling technique of simple random sampling type so that a sample of 38 respondents was determined. The data collection technique used in this research is the distribution of questionnaires using google form. The data analysis technique used is Structural Equation Modeling (SEM) using partial least square (PLS).